Regulation and Supervision of Islamic Banks - Mejia, Aledjandro Lopez (IMF Working Papers; Working Paper, 2014)
This paper aims at developing a better understanding of Islamic banking (IB) and providing policy recommendations to enhance the supervision of Islamic banks (IBs). It points out and discusses similarities and differences of IBs with conventional banks (CBs) and reviews whether the IBs are more stable than CBs. Given the risks faced by IBs, the paper concludes that they need a legal, corporate and regulatory framework as much as CB does. The paper also argues that it is important to ensure operational independence of the supervisory agency, which has to be supported by adequate resources, a sound legal framework, a well designed governance structure, and robust accountability practices.